Optimization of Chitosan-Based Edible Film with the Addition of Velvet Bean Aqueous Extract and Cinnamon Essential Oil for Antibacterial Packaging - Ariani, Sri Retno Dwi; Sholihah, Khoirur Rohmaniatush; Susilowati, Endang; Setyowati, Widiastuti Agustina Eko; Munifah, Ifah; Rohmatun, Tyas Dwi; Safitri, Nadia Indri (Molekul, 2025)
ABSTRACT. The current global warming issue has encouraged a lot of research on edible films. The use of edible films has become an international trend and is now essential for our products to compete in the global market. Bioactive compounds from plants can be incorporated into edible films to enhance their biological activity, including their antibacterial properties. This study developed a chitosan-based edible film with the addition of velvet bean aqueous extract (VAE) and cinnamon essential oil (CEO), aiming for high antibacterial activity. The objectives of this study were to isolate and identify the chemical components of CEO, test its antibacterial activity, find the most optimum formulation of a chitosan-based edible film with VAE and CEO in terms of antibacterial activity (Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 25923), and analyze the physical and morphological properties of the resulting edible film. The research methods included a literature review and laboratory experiments, with procedures involving the isolation and GC-MS-based identification of CEO chemical components, antibacterial activity testing of CEO, optimization of a chitosan-based edible film formulation with the addition of VAE and CEO based on antibacterial activity test against E. coli ATCC 25922 and S. aureus ATCC 25923 (well diffusion method), and characterization of the best film’s physical properties (thickness, tensile strength, elongation, solubility, WVP, and WVTR) and morphological analysis (SEM method). The results of this study were as follows: (a) CEO contained cinnamaldehyde (52.86%) and 2- methoxycinnamaldehyde (47.06%); (b) CEO had very strong antibacterial activity against E. coli ATCC 25922 and S. aureus ATCC 25923, with inhibition zones of 46.28 mm and 47.95 mm, respectively; (c) the most optimal edible film formulation consisted of chitosan with 30.0% VAE and 4.0% CEO, yielding strong antibacterial activity against E. coli ATCC 25922 (15.50 mm inhibition) and S. aureus ATCC 25923 (16.71 mm inhibition), with a thickness of 0.15 mm, tensile strength of 0.32 Mpa, elongation of 0.32%, solubility of 4.89%, WVP of 8.82 g/m2.h), and WVTR of 3.92 g/m.h. Morphological analysis of the edible film showed a relatively flat and smooth surface with minor cracks in some areas. Keywords: antibacterial packaging, chitosan, cinnamon essential oil, edible film, velvet bean aqueous extract